Photon correlation spectroscopy of particle size distribution of solid matter; Проблемы геологии и освоения недр; Т. 2 - Dozmorov P. S. Pavel Sergeevich (Geology, mining and petroleum engineering (English, German), 2012)
Заглавие с титульного листа